2014
DOI: 10.1371/journal.pone.0088288
|View full text |Cite
|
Sign up to set email alerts
|

Morphology of Influenza B/Lee/40 Determined by Cryo-Electron Microscopy

Abstract: Cryo-electron microscopy projection image analysis and tomography is used to describe the overall architecture of influenza B/Lee/40. Algebraic reconstruction techniques with utilization of volume elements (blobs) are employed to reconstruct tomograms of this pleomorphic virus and distinguish viral surface spikes. The purpose of this research is to examine the architecture of influenza type B virions by cryo-electron tomography and projection image analysis. The aims are to explore the degree of ribonucleoprot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 32 publications
(37 reference statements)
0
26
0
Order By: Relevance
“…The impact of virion morphology on the stability of particles during manufacturing is not well understood but vaccine manufacturers prefer candidate vaccine viruses that yield spherical particles [47]. Unstable filamentous virions are produced as a result of mutations in the M2 cytoplasmic tail [48].…”
Section: Discussionmentioning
confidence: 99%
“…The impact of virion morphology on the stability of particles during manufacturing is not well understood but vaccine manufacturers prefer candidate vaccine viruses that yield spherical particles [47]. Unstable filamentous virions are produced as a result of mutations in the M2 cytoplasmic tail [48].…”
Section: Discussionmentioning
confidence: 99%
“…Further experiments using labelled vRNPs (Lakdawala et al, 2014) could address this. Furthermore, while electron microscopic comparisons of vRNP structural arrangement in influenza A and B virions might suggest different mechanisms of genome packaging between the two viruses (Katz et al, 2014;Noda et al, 2006), our results suggest a similar mechanism of cis-acting RNA signal-mediated packaging is employed by both viruses. The difference in vRNP arrangement is likely due to vRNA-vRNA interactions differing between the two viruses, leading to the more twisted vRNP complex observed in influenza B viruses.…”
mentioning
confidence: 56%
“…Electron microscopic analysis of influenza A virus particles demonstrated that the vRNPs are arranged in a highly ordered '7+1' orientation in which all segments align in a circular fashion with one segment in the centre (Noda et al, 2006). However, recent evidence suggests that this does not occur in influenza B viruses, as the vRNPs appear to twist around each other (Katz et al, 2014). This suggests that influenza A and B viruses potentially adopt different mechanisms for genome packaging.…”
Section: Introductionmentioning
confidence: 99%
“…Shape identification can thus be achieved by classifying the observed incomplete PG (which can be subject to measurement error) to one of the reference polyhedra. Apart from BMCs, these techniques could potentially also be applied to other biological objects exhibiting polyhedral structure, such as several types of viruses [ 1 , 7 , 9 , 10 ] and protein complexes such as clathrin [ 11 ].…”
Section: Introductionmentioning
confidence: 99%